Post-void residual urine ratio: A novel clinical approach to the post-void residual urine in the assessment of males with lower urinary tract symptoms - Rubilotta, Emanuele (Investig Clin Urol, 2021)
PURPOSE: To assess the correlation between post-void residual urine ratio (PVR-R) and pathological bladder emptying diagnosed by pressure-flow studies (PFS) in males with lower urinary tract symptoms (LUTS). MATERIALS AND METHODS: PVR-R and PVR urine were evaluated in 410 males underwent PFS for LUTS. PVR-R was the percentage of PVR to bladder volume (voided volume+PVR). Schafer and International Continence Society (ICS) nomograms, Bladder Contractility Index (BCI) were used to diagnose bladder outlet obstruction (BOO) and detrusor underactivity (DUA). We subdivided the cohort in 4 groups: Group I, BOO+/DUA+; Group II, BOO-/DUA+; Group III, BOO+/DUA−; Group IV, BOO−/DUA− (control group). We subdivided the 4 groups according to PVR-R strata: (1) 0%–20%; (2) 21%–40%; (3) 41%–60%; (4) 61%–80%; (5) 81%–100%. RESULTS: Group I had a greater median PVR-R (50%) with a >40% in 61.4% of the cohort. Median PVR-R was 16.6% in Group II, 24% in Group III, and 0% in the control Group. According to ICS nomograms and BCI, median PVR-R and PVR were significantly higher (p<0.001) in obstructed and underactive males. PVR-R threshold of 20% allowed to recognize males with voiding disorders with high sensibility, specificity, PPV, and NPV. A PVR-R cut-off of 40% identified males with associated BOO and DUA and more severe voiding dysfunction. CONCLUSIONS: A higher PVR-R is related to a more severe pathological bladder emptying, and to the association of BOO and DUA. PVR-R may have a clinical role in first assessment of males with LUTS and severe voiding dysfunction.